Investigating Students’ Intention to use Digital Securities Platforms: a Perspective from the TAM and UTAUT Frameworks - Anita Tarihoran; Ahmad Kodri Fauzi Hasibuan; Iskandar Muda (International Journal of Management, Economic and Accounting, 2026)
This study aims to analyze the effects of performance expectancy, effort expectancy, social influence, and facilitating conditions on students’ intention to use digital securities platforms at Universitas Mikroskil. This research adopts an associative research design with a quantitative approach. Primary data were collected through a closed-ended questionnaire using a five-point Likert scale. The population of this study consists of all students of Universitas Mikroskil, and the sampling technique employed was purposive sampling. The minimum sample size was determined using the Slovin formula, resulting in 96 respondents who met the research criteria. Data analysis was conducted using Structural Equation Modeling (SEM) with the assistance of LISREL software. The results indicate that social influence and facilitating conditions have a positive and significant effect on the intention to use digital securities platforms, while performance expectancy and effort expectancy do not have a significant effect on the intention to use digital securities platforms.